Data Structures Using C. - Bandyopadhyay, Samir Kumar; De, Kashi Nath. (2008)
Data Structures Using C brings together a first course on data structures and the complete programming techniques, enabling students and professionals implement abstract structures and structure their ideas to suit different needs. This book elaborates the standard data structures using C as the basic programming tool. It is designed for a one semester course on Data Structures.
12.6.1 Inserting a Node Into an AVL Tree -- 12.6.2 Deleting a Node from an AVL Tree -- 12.7 B-Trees -- 12.7.1 Generation of a B-Tree -- 12.7.2 Searching for a Key in B-Tree -- 12.7.3 Inserting a Key into B-Tree -- 12.7.4 Deleting a Key from B-Tree -- Exercises -- Chapter 13: Graphs -- 13.1 Introduction -- 13.2 Graph Fundamentals -- 13.3 Graph Representation -- 13.3.1 Adjacency Matrix -- 13.3.2 Adjacency Lists -- 13.4 Graph Traversal -- 13.4.1 Breadth-First Search -- 13.4.2 Depth-First Search -- Exercises -- Index.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books